2013
DOI: 10.4314/tjpr.v12i5.16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Clinical Study on the Effectiveness of Homeopathic Combination Remedy with Standard Maintenance Therapy for Dengue Fever

Abstract: (53.50 ± 0.02) x 10 4 to (79.40 ± 0.02) x 10 4 /µL, but decreased HCT from 42.30 ± 2.48 to 39.68 ± 4.35 %. A significant difference was seen in the PLT count, WBC and HCT level between the two therapies (p = 0.012, 0.003 and 0.021, respectively). Conclusion:The homeopathic combination appeared to be a more potent treatment against dengue fever; however, further studies are required to demonstrate this clearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 6 publications
3
16
0
2
Order By: Relevance
“…As a TM in Europe and many other countries worldwide, homeopathy was used in history 6 during the epidemics of scarlet fever, 7 Spanish influenza, 8 Chikungunya fever, 9,10 dengue fever, 11,12 leptospirosis, 13 and malaria, 14 for example. Given the paucity of strongly evidence-based regimens for conventional vaccines and anti-viral medication in the current COVID-19 pandemic, homeopathy has been used, respectively, by 4-5% and 45-50% of the populations in Hong Kong and its adjacent city, Macau; it has been used as an adjunctive measure in the management of influenza-like diseases alongside conventional medicine or TCM.…”
mentioning
confidence: 99%
“…As a TM in Europe and many other countries worldwide, homeopathy was used in history 6 during the epidemics of scarlet fever, 7 Spanish influenza, 8 Chikungunya fever, 9,10 dengue fever, 11,12 leptospirosis, 13 and malaria, 14 for example. Given the paucity of strongly evidence-based regimens for conventional vaccines and anti-viral medication in the current COVID-19 pandemic, homeopathy has been used, respectively, by 4-5% and 45-50% of the populations in Hong Kong and its adjacent city, Macau; it has been used as an adjunctive measure in the management of influenza-like diseases alongside conventional medicine or TCM.…”
mentioning
confidence: 99%
“…However, the latter study was conducted on mild-risk patients only. 19 In another comparative study of prophylactic transfusion versus supportive care alone, no difference in mean daily platelet count was found between the two groups. 8 However, our study, having the same assessment parameter, showed significant difference in favor of adjunctive homeopathy (p < 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…17 Jacobs et al 18 conducted a pilot study with a homeopathic combination for dengue fever symptoms: the results were inconclusive. Saeed-ul-Hassan et al 19 conducted a comparative study to assess the effect of a different homeopathic combination on platelet count and found encouraging results, showing improvement in platelet count. Further, Mahesh et al 20 reported homeopathic treatment of 10 dengue fever cases with positive outcome.…”
Section: Introductionmentioning
confidence: 99%
“…O resultado da busca eletrônica (Tabelas 1 e 2) mostra que todos os estudos foram publicados a partir do ano 2000. No total, foram identificados 24 diferentes estudos, sendo selecionados 13 16,[21][22][23][24][25][26][27][28][29][30][31][32] ; no entanto, apenas 4 tratavam de estudos de intervenção concluídos, sendo 1 único ensaio clínico controlado e aleatorizado 21 , 1 estudo comparativo sem informações quanto à aleatorização e cegamento 32 , e 2 ensaios de comunidade 27,28 (Tabela 1), todos publicados em língua inglesa, sendo que houve concordância completa entre os autores quanto aos aspectos avaliados em cada estudo em todas as fases da revisão. Três desses estudos foram publicados em periódicos especializados em homeopatia e um estudo foi publicado em um periódico voltado à pesquisa farmacêutica.…”
Section: Resultsunclassified
“…O estudo de Saeed-ul-Hassan et al 32 28 , o custo financeiro relativo à administração de um medicamento homeopático para a prevenção da dengue é inferior a um centavo de dólar norte-americano e equivalente a US$ 1,75 para o tratamento da doença. Portanto, se comprovada sua eficácia, a homeopatia poderia ser uma alternativa viável e de baixo custo para o seu controle.…”
Section: Resultsunclassified